The Right of Secession in Burma's First Constitution - Hauret, Philip (Advances in Social Sciences Research Journal, 2024)
An agreement between Burmese nationalists and the British government in early 1947 set forth the basic steps of an “independence roadmap” designed to not only take Burma to full independence via a democratic process, but to unify Burma Proper and the Frontier areas under a governmental system the Frontier peoples would help to craft. However, the semi-federal constitution adopted in 1947, which granted two minorities a right of secession, failed in its role of achieving the second of these lofty objectives, for by the early 1960’s several of the major frontier peoples were in revolt, while those still loyal to the government sought to fundamentally reform it. This paper explores the role of the constitutional right of secession in the creation of the Union of Burma, why only two of the major minorities received it and how the right became a political liability for both. It also explores how it was used to justify the military’s permanent entry into the political arena in 1962, not with an intent to stabilize it temporarily as in 1958, but to replace it entirely with one more to its liking.